Sexually transmitted infections in HIV-infected patients in Kabale Hospital, Uganda - Osinde, Michael Odongo; Kakaire, Othman; Kaye, Dan Kabonge (The Journal of Infection in Developing Countries, 2011)
Introduction: Acquisition of sexually transmitted infections (STIs) is an epidemiological marker of high-risk sexual behavior in HIV-infected patients. We assessed the prevalence of STIs among patients attending an HIV care and support centre. Methodology: From January to August 2009, we assessed socio-demographic variables, sexuality, disclosure of sero-status and STI treatment for 400 patients attending the HIV care and support centre. Characteristics of those who had been treated and those who had never been treated for STIs were compared to identify factors independently associated with STIs. Results: Of the 400 respondents, 25.3% were male, 47.3% were aged 25-34 years, over 85% were currently married or had ever been married, and 62% had primary level of education or less. Though 82.5% were on antiretroviral drugs, only 53.1% disclosed their sero-status to their regular partners and only 41.9% knew the sero-status of their regular partners. Furthermore, 151 (37.7%) had been treated for STIs. The STIs were gonorrhoea (15; 9.7%), chlamydia (11; 7.1%), Trichomonas vaginalis (5; 3.3%), syphilis (99; 64.3%), and mixed infections (21; 13.6%). Factors associated with STI treatment on univariable analysis were age at sexual debut, whether the respondent had had sex in the previous six months, frequency of sexual intercourse, having changed sexual partners, number of sexual partners, and age when the respondent had a first child. Conclusion: Unprotected sexual intercourse and STIs are common among patients seeking HIV care in Uganda. Only the age of sexual debut (odds ratio0.82, confidence limits 0.71, 0.94) was independently (though inversely) associated with STIs.